Economic analysis of aquaculture enterprises and determination of factors affecting sustainability of the sector in Turkey - Arikan, Mehmet Saltuk; Aral, Yilmaz (Ankara Univ Press, 2019)
This research was conducted to carry out technical and economic analysis of the aquaculture enterprises in Mugla as well as to determine the factors affecting sustainability in the sector. The research material is the production data of 65 enterprises from 2014-2015 years activity period. Stratified random sampling method was used for the determination of the enterprises involved in this study and the data provided by using the data collection form with face-to-face interview. The production data of the enterprises are evaluated from the technical and economical perspectives and the factors that impact the unit profit are estimated by the multiple regression model. The average fattening period (months), the rate of shrinkage and mortality (%), and the FCR (kg feed/kg fish) for Seabream and Seabass were found to be 14.43-19.05; 10.70-14.33 and 1.84-1.98 respectively, among the enterprises. The unit cost and unit profit for the fish species in question were estimated to be 4.18 US$/kg and 4.57 US$/kg, and 1.29 US$/kg and 1.07 US$/kg, respectively. According to the estimated regression model; production type, capacity utilization rate, sales price and FCR are determined to be effective on the unit profit. It was concluded that aquaculture enterprises could achieve sustainability if; i) capacity utilisation rate was optimised; ii) dependence on foreign sources of feed and raw materials was reduced; iii) producer organisations played a more active role in the market; iv) a regulatory authority body was established to balance out prices and v) export opportunities were pursued further in foreign markets.
Türkiye’de kültür balıkçılığı işletmelerinin ekonomik analizi ve sektörde sürdürülebilirlik üzerine etkili faktörlerin belirlenmesi
Keywords: Aquaculture enterprises; economic analysis; regression analysis; sustainability; Turkey